2017
DOI: 10.1091/mbc.e17-03-0195
|View full text |Cite
|
Sign up to set email alerts
|

Human adenine nucleotide translocases physically and functionally interact with respirasomes

Abstract: A network of interactions for human adenine nucleotide translocases, required for oxidative phosphorylation, is reported. Of particular interest is an evolutionarily conserved and functionally important association with respiratory supercomplexes, which is surprising because the respirasomes of yeast and mammals are different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 81 publications
3
53
2
Order By: Relevance
“…However, it remains possible that these transporters can also export matrix copper and that our current assays lack the necessary components either in small molecules or interacting protein partners to stimulate this activity. SLC25A3 has been identified in multiple complexes in the IM, including the ATP synthasomes and respirasomes (42)(43)(44). The physical association of the respiratory chain complexes with other MCFs, most notably ANT1, is known to significantly affect both nucleotide transport rates and oxidative phosphorylation (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it remains possible that these transporters can also export matrix copper and that our current assays lack the necessary components either in small molecules or interacting protein partners to stimulate this activity. SLC25A3 has been identified in multiple complexes in the IM, including the ATP synthasomes and respirasomes (42)(43)(44). The physical association of the respiratory chain complexes with other MCFs, most notably ANT1, is known to significantly affect both nucleotide transport rates and oxidative phosphorylation (44).…”
Section: Discussionmentioning
confidence: 99%
“…SLC25A3 has been identified in multiple complexes in the IM, including the ATP synthasomes and respirasomes (42)(43)(44). The physical association of the respiratory chain complexes with other MCFs, most notably ANT1, is known to significantly affect both nucleotide transport rates and oxidative phosphorylation (44). Therefore, further work is needed to elucidate the other components of this pathway involving SLC25A3, including the identity of possible metabolic products that could serve as modulators of transport and other transporters required to redistribute copper to the IMS.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found similar stability with oxidative phosphorylation proteins [17]. Two inhibitors of ANT exist, both blocking the ADP/ATP transport function: carboxyatractyloside (CATR) which is cell membrane-impermeable and bongkrekic acid (BKA), which is membrane-permeable.…”
Section: Ant Regulates Cellular Respiration and Atp Productionmentioning
confidence: 86%
“…hANT1 is mainly ex-pressed in terminally differentiated muscle cells; hANT2 is growth-regulated and is upregulated in highly glycolytic and proliferative cells; and hANT3 is considered to be ubiquitous and non-specifically regulated [30]. The protein partners of the isoforms were found to be similar, and the absence of the main isoform hANT3 had no impact on the oxidative phosphorylation process [31]. However, the isoforms were found to be de-regulated in human tumors [2].…”
Section: Dissimilar Functions Of the Same Protein Isoformsmentioning
confidence: 95%